GE_GERICHTE C/18198/2014 vom 30. Oktober 2015 - GE Cour de justice (2015)
PROCÉDURE SOMMAIRE; CONCLUSIONS; FORMALISME EXCESSIF; FAILLITE SANS POURSUITE PRÉALABLE; SURSIS CONCORDATAIRE | LP.174; LP.190; LP.192; LP.293; LP.293a; LP.293d; LP.294; LP.296b; LP.298